2022
DOI: 10.3390/geomatics2040028
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Connectivity and Spread Pathways of Land Use/Cover Change in a Transboundary Basin Based on the Circuit Theory

Abstract: Understanding the spatial spread pathways and connectivity of Land Use/Cover (LULC) change within basins is critical to natural resources management. However, existing studies approach LULC change as distinct patches but ignore the connectivity between them. It is crucial to investigate approaches that can detect the spread pathways of LULC change to aid natural resource management and decision-making. This study aims to evaluate the utility of the Circuit Theory to detect the spread and connectivity of LULC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…In recent years, many studies have found rational land use allocation is key to controlling NPS pollution output [7]. Ongoing human modifications to the land use system bring about changes in surface vegetation types, consequently impacting surface runoff dynamics [8,9]. For example, the presence of agriculture in the vicinity of water resources raises the concentration of sediments and nutrients in the water and accelerates the flow of NPS pollutants, ultimately affecting the water quality within the watershed [10].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have found rational land use allocation is key to controlling NPS pollution output [7]. Ongoing human modifications to the land use system bring about changes in surface vegetation types, consequently impacting surface runoff dynamics [8,9]. For example, the presence of agriculture in the vicinity of water resources raises the concentration of sediments and nutrients in the water and accelerates the flow of NPS pollutants, ultimately affecting the water quality within the watershed [10].…”
Section: Introductionmentioning
confidence: 99%